Perlindungan Hukum Merek Terkenal di Indonesia - Ridwan Khairandy (Jurnal Hukum IUS QUIA IUSTUM, 1999)
Indonesian Trade mark law related to the represive protection limits it self to the legal protection for like products or sen/ices. In fact, here have bee many products or services using illegal well-know marks for unlike products orsen/ices. Before law 1992 No. 19 jo law 1997No. 14, in many cases, courts extended legal protection to include legal protection forwell-know marks of both like and unlike products. The courts based their considerations upon good faith principle